Interplay of collective electrostatic effects and level alignment dictates the tunneling rates across halogenated aromatic monolayer junctions - Chen, Xiaoping; Zharnikov, Michael (The journal of physical chemistry letters, 2019)
Predictions about the electrical conductance across molecular junctions based on self-assembled monolayers (SAMs) are often made from the SAM precursor properties. Collective electrostatic eﬀects, however, in a densely packed SAM can override these predictions. We studied, experimentally and theoretically, molecular tunneling junctions based on thiolate SAMs with an aromatic biphenyl backbone and variable, highly polarizable halogen termini X (S-(C6H5)2X; X = H, F, Cl, Br, or I). We found that the halogen-terminated systems show tunneling rates and dielectric behavior that are independent of X despite the large change in the electronegativity of the terminal atom. Using density functional theory, we show that collective electrostatic eﬀects result in modulations of the electrostatic potential that are strongly conﬁned spatially along the direction of charge transport, thereby rendering the role of the halogen atoms insigniﬁcant for SAMs with conjugated backbones.